2020
DOI: 10.1111/bjd.19042
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of eribulin mesylate for patients with cutaneous angiosarcoma previously treated with taxane: a multicentre prospective observational study

Abstract: Summary Background Taxanes are the current first‐line treatment for advanced cutaneous angiosarcoma (CAS) for patients who are considered difficult to treat with doxorubicin owing to advanced age or comorbidity. However, no effective second‐line therapy for such patients has been established. Methods We designed a single‐arm prospective observational study of eribulin mesylate (ERB) administered at a dose of 1·4 mg m−2 on days 1 and 8 in a 21‐day cycle. Patients with advanced CAS who were previously treated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 52 publications
1
30
0
1
Order By: Relevance
“…Le Cesne et al reported in a French retrospective study that the 3month PFS rate when trabectedin was administered among angiosarcoma patients was 25% [15]. Further, treatment with eribulin mesylate helped achieve a 3month PFS, 8.6-month OS, and 20% overall response rate in a prospective observational study [16].…”
Section: Discussionmentioning
confidence: 96%
“…Le Cesne et al reported in a French retrospective study that the 3month PFS rate when trabectedin was administered among angiosarcoma patients was 25% [15]. Further, treatment with eribulin mesylate helped achieve a 3month PFS, 8.6-month OS, and 20% overall response rate in a prospective observational study [16].…”
Section: Discussionmentioning
confidence: 96%
“…The efficacy of eribulin mesylate 7 and immune checkpoint inhibitors 8 on angiosarcoma was recently reported. Few studies have reported the effects of these drugs for controlling recurrent and bleeding local lesions such as those observed in our patient.…”
Section: Discussionmentioning
confidence: 99%
“…However, treatment duration of eribulin in those 3 patients was less than 9 months. Fujisawa et al showed the promising efficacy of eribulin for treating patients with advanced cutaneous AS who previously received taxanes (26). The best overall response rate was 20%, and the median overall survival and progression-free survival were 8.6 and 3.0 months, respectively.…”
Section: Discussionmentioning
confidence: 99%